POTENSI Acrostichum aureum L. (PTERIDACEAE) SEBAGAI BIOAKUMULATOR LOGAM BERAT MANGAN (Mn) DAN TEMBAGA (Cu): Potential of Acrostichum aureum L. (Pteridaceae) as Heavy Metal Manganese (Mn) and Copper (Cu) Bioaccumulator - Sanubari, Meirina Orchidanti; Sedayu, Agung; Miarsyah, Mieke (Bioma, 2016)
Acrostichum aureum L. is a fern from family Pteridaceae, commonly called as swamp fern or mangrove fern and usually found in mangrove, swamp or brackish area. It noted that heavy metal concentration was found in Acrostichum aureum, but distinction measure in each organs was unknown. This study was conducted to acquire information about heavy metal concentration in Acrostichum aureum, the differential expression of Mn and Cu concentration in each organs, and examine the potential of Acrostichum aureum as Mn and Cu bioaccumulator. Acrostichum aureum and sediment sample taken from Muara Angke Wildlife Reserve, North Jakarta which contaminated by heavy metal Mn and Cu. As a proponent data, Acrostichum aureum and sediment sample also taken from Gunung Kapur Ciseeng that assumpted as uncontaminated area. The methods used was descriptive with purposive sampling technique. The result showed that Acrostichum aureum was bioaccumulator for Mn with BCF average value 1.06. Organs with the highest Mn and Cu concentration was root. U-Mann Whitney test result showed that Mn and Cu concentration in each lower organs significantly different to the upper organs.